(untitled) (International Journal of Engineering and Computer Science, 2013)
The least significant bit (LSB) based approach is a popular type of steganographic algorithms in the spatial domain. The advantage of LSB is its simplicity to embed the bits of the message directly into the LSB plane of cover-image and many applications use this method. In this paper we try to give an overview of different LSB methods and there advancements